Penentuan Kebutuhan Air dan Koefisien Tanaman (Kc) Padi (Oryza sativa L.) di Sawah Lahan Rawa Lebak - Feldy Khalid; Edward Saleh; Rahmad Hari Purnomo (Seminar Nasional Lahan Suboptimal, 2019)
Khalid F, Saleh E, Purnomo RH.  2019. The determination of water requirement and crop coefficient (Kc) of paddy (Oryza sativa L.) in swampy land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang  4-5 September 2019. pp. 140-156. Palembang: Unsri Press.This research aimed to determine the water requirement and coefficient of paddy in swampy land. This research was conducted from January to June 2019. The research used an experimental method with descriptive data presented in the form of tables and graphs. The results showed that the net water requirement from the initial season, crop development, mid season and late season were 1.05 mm/day, 4.64 mm/day, 11.20 mm/day and 18.72 mm/day. The evapotranspiration measurements results (ETc) from the initial season, crop development, mid season and late season were 1.23 mm/day, 2.57 mm/day, 2.64 mm/day and 1,57 mm/day, for plant coefficients (Kc) respectively were 0.42; 0.89; 1.01 and 0.62. The largest evapotranspiration values and plant coefficient were occured during the growth period of 31 to 65 days or mid season.Keywords:  net water requirements, evapotranspiration, coefficient of crops, percolation, swampy land